2023
DOI: 10.1021/jacs.3c07804
|View full text |Cite
|
Sign up to set email alerts
|

Refined Electrolyte and Interfacial Chemistry toward Realization of High-Energy Anode-Free Rechargeable Sodium Batteries

Yu-Ying Zhang,
Chao-Hui Zhang,
Yu-Jie Guo
et al.

Abstract: Anode-free rechargeable sodium batteries represent one of the ultimate choices for the ‘beyond-lithium’ electrochemical storage technology with high energy. Operated based on the sole use of active Na ions from the cathode, the anode-free battery is usually reported with quite a limited cycle life due to unstable electrolyte chemistry that hinders efficient Na plating/stripping at the anode and high-voltage operation of the layered oxide cathode. A rational design of the electrolyte toward improving its compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Na-ion batteries (NIBs) have received great attention in large-scale energy storage systems and smart grids because of huge abundance and low cost of sodium sources. Substantial efforts have been devoted to developing cost-effective and high-performance cathodes these years toward commercially available NIBs. Particularly, the benign and cheap iron-based phosphates were regarded as one of the best choices for NIBs as parallel LiFePO 4 cathodes have gained huge commercial success in lithium-ion batteries. However, the olivine-NaFePO 4 candidates could not be directly obtained by the conventional ceramic method due to the unfavorable thermodynamics feature and trend to transform into the more stable maricite phase. , Unfortunately, the maricite-type NaFePO 4 is usually believed to be of electrochemical inertness due to absence of effective Na + ion diffusion channels .…”
Section: Introductionmentioning
confidence: 99%
“…Na-ion batteries (NIBs) have received great attention in large-scale energy storage systems and smart grids because of huge abundance and low cost of sodium sources. Substantial efforts have been devoted to developing cost-effective and high-performance cathodes these years toward commercially available NIBs. Particularly, the benign and cheap iron-based phosphates were regarded as one of the best choices for NIBs as parallel LiFePO 4 cathodes have gained huge commercial success in lithium-ion batteries. However, the olivine-NaFePO 4 candidates could not be directly obtained by the conventional ceramic method due to the unfavorable thermodynamics feature and trend to transform into the more stable maricite phase. , Unfortunately, the maricite-type NaFePO 4 is usually believed to be of electrochemical inertness due to absence of effective Na + ion diffusion channels .…”
Section: Introductionmentioning
confidence: 99%
“…However, most fluorinated diluents cannot dissociate potassium salts, preventing an effective increase in the K + transference number. Recently, several different strategies have been reported to improve the solvated structure of electrolytes. Several key studies illustrate the development of the solvated structure of electrolytes, demonstrate the realization of WSEs, and improve the electrochemical properties. , It has been shown that the interaction between solvent molecules can regulate solvated structures. Furthermore, systematic changes in the molecular skeleton of ethers have a profound effect on the chelation behavior of [K + –solvent] and the electrochemical stability of electrolytes . For example, shortening the alkyl chain in the middle of DME reduces the chelating ability, while extending it at its end increases the spatial site resistance. , These strategies share a common core of altering the coordinated environment around K + to promote the formation of WSEs .…”
Section: Introductionmentioning
confidence: 99%
“…Severe side reactions of Na metal with electrolyte and uncontrolled Na dendrites stemming from uneven Na deposition lead to fast depletion of active Na and electrolyte, resulting in inferior cycling stability, and even safety hazards . Many methods have been tried to resolve these issues from multiple aspects, such as adjusting the components of electrolyte solvent from ester to ether to inhibit side reactions, , developing functional electrolyte additives to build stable SEI, , and modifying the current collector to regulate the nucleation and growth of Na metal deposits. , Among these methods, multidimensional current collectors with large surface areas can provide enough nucleation sites for uniform electrodeposition and limit the volume change stemming from sodium plating and stripping . Wu et al devised core–shell C@Sb nanoparticles to compose a nucleation buffer layer for homogeneous electrochemical deposition of sodium metal .…”
mentioning
confidence: 99%